(untitled) (Arsi Journal of Science and Innovation, 2025)
Abstract This research deals with the discourse analysis as to ‘waa sadii’s’ witty speech among the Arsi Oromo, Ethiopia. ‘Waa sadii’ (which literally mean three things) is an oral speech art which is frequently used in discourse to express people’s oral communication analogically. In addition to its artistic nature, ‘Waa sadii’ does have also a poetic and prose nature. On the process of uttering a speech, the five sense organs of a conveyer should be active. This research paper aims at describing the symbolic value and importance of ‘waa sadii’ in enhancing the educational and entertainment skills in social and natural environments of the Arsi Oromo. Ethnographic methods of data gathering were employed in generating relevant data from primary and secondary sources. Researchers have spent some time as to the research area to collect data. Interpretive approach was used to analyze data. The analysis showed that the witty speech among the Arsi Oromo involves both social-cultural and natural phenomena. Items which signify ‘waa sadii’ are presented mysteriously and symbolically in line with the value system of the people and the physical character of the part. ‘Waa sadii’ also involves analogical representations of symbols vis a vis their type, size, shape, color, organization, co-affiliation, rank, and the like. ‘Waa sadii’ is one of the mechanisms commonly used to teach young people the knowledge of their social behavior and environment vital for their future achievement. The study concluded that the witty speech/waa sadii/ is a traditional oral art which is still playing a pivotal role in shaping the day today activities or lives of Arsi people. Now days, Arsi Oromo practice it so especially in educating children to have a good understanding of their social and physical environments. They are also adapted to the changing world. The study mainly indicated the importance of contextualizing such witty speech in teaching literature to make education affordable and enjoyable.